2018
DOI: 10.1590/2179-8087.026116
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cardboard Disks for Crowning Seedlings in Reforestation

Abstract: The present study aimed to evaluate the effect of chemopreventive or water-repellent substances on the durability of cardboard disks used to crown forest tree species. The experiment presented a randomized block design with four repetitions and four sampling times (63, 133, 260 and 365 days) and was installed in Seropedica, RJ, in an area with Urochloa humidicola. Bamboo poles were used to simulate seedlings in the field and define the position of the experimental units. The treatments consisted of in natura c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 4 publications
0
6
0
2
Order By: Relevance
“…Cardboard can be also effective in controlling soil temperature affecting plant growth over time (Benites et al, 2020), since many nutrients essential for its development are only released at certain temperature ranges (Gasparin et al, 2005). A strong effect of cardboard mulching on soil temperature was noted on days with high air temperatures, which proved up to 15 °C lower in the 0 to 10 cm deep layer compared to bare soil (hoe crowning) areas (Silva et al, 2018). This cardboard effect may have consequences on seedlings development under field conditions, given that it improves the soil environment for rooting due, for instance, to less water loss and more favorable conditions for biological activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cardboard can be also effective in controlling soil temperature affecting plant growth over time (Benites et al, 2020), since many nutrients essential for its development are only released at certain temperature ranges (Gasparin et al, 2005). A strong effect of cardboard mulching on soil temperature was noted on days with high air temperatures, which proved up to 15 °C lower in the 0 to 10 cm deep layer compared to bare soil (hoe crowning) areas (Silva et al, 2018). This cardboard effect may have consequences on seedlings development under field conditions, given that it improves the soil environment for rooting due, for instance, to less water loss and more favorable conditions for biological activity.…”
Section: Resultsmentioning
confidence: 99%
“…Several previous studies have shown the efficiency of cardboard crowning to control exotic grasses in reforestation projects. Silva et al (2018) showed, through photo documentation, that cardboard was effective at controlling Urochloa humidicola growth up to a year after its placement on the ground. Gonçalves et al (2018) succeded in controlling Andropogon bicornis with cardboard crowning in a reforestation in Seropédica, RJ, while Benites et al (2020) also succeded in controlling Urochloa decumbens (Stapf) R.D.Webster and Paspalum notatum Flüggé (Poaceae) using the same method in the Cerrado of the Mato Grosso do Sul state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Como a presença de plantas daninhas nos povoamentos florestais tende a durar por períodos superiores a dois anos (Resende & Leles, 2017), concluise que o papelão teve pouca duração em campo. Silva et al (2018) avaliaram diferentes tratamentos químicos em discos de papelão em relação à degradação. O estudo foi realizado no município de Seropédica, RJ, que apresenta precipitação média anual de 1.354 mm.…”
Section: Counclassified
“…Dentre as operações para controle de plantas daninhas que mais necessitam de mão de obra, tem-se a roçada semimecanizada e coroamento manual (Eloy et al, 2014). Em vista da necessidade de buscar alternativas, uma opção seria a utilização de papelão para o coroamento das mudas recém-plantadas em campo (Gonçalves et al, 2018;Silva et al, 2018). Essa técnica tem como objetivo promover o coroamento artificial das mudas, eliminando a necessidade de coroamentos manuais realizados com enxada.…”
unclassified